PENGETAHUAN MITIGASI BENCANA KEBAKARAN HUTAN DAN LAHAN SISWA KELAS V SEKOLAH DASAR NEGERI 6 PEKANBARU - Lastri Lestari; Eddy Noviana; Zetra Hainul Putra (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The Purpose of this study was to investigate fifth grade students knowledge of forest and land fire disaster mitigation from a Public Primary School (SDN 6 Pekanbaru) Riau. Students knowledge of mitigation is categorized from four levels; Excellent, good, sufficient, foor. This study applies a descriptive quantitative method. This studies was conducted with 111 fifth grade students from SDN 6 Pekanbaru. The instrument used to collect data was 24 items of knowledge tests on forest and land fire disaster mitigation which consisted of tes items in the form of multiple choice. That students’ knowledge of forest and land fire disaster mitigation is in the sufficient category with an average of 50,55.Key Words: Knowledge, Disaster Mitigation, Forest and Land Fires, Descriptive Quantitative.